Fundamental World of Quantum Chemistry 2004
DOI: 10.1007/978-94-017-0448-9_5
|View full text |Cite
|
Sign up to set email alerts
|

On Supersymmetric Quantum Mechanics

Abstract: This paper constitutes a review on N = 2 fractional supersymmetric Quantum Mechanics of order k. The presentation is based on the introduction of a generalized Weyl-Heisenberg algebra W k. It is shown how a general Hamiltonian can be associated with the algebra W k. This general Hamiltonian covers various supersymmetrical versions of dynamical systems (Morse system, Pöschl-Teller system, fractional supersymmetric oscillator of order k, etc.). The case of ordinary supersymmetric Quantum Mechanics corresponds to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…The A {κ} r-parameter algebra covers the cases of (i) the extended harmonic oscillator algebra [21], (ii) the fractional oscillator algebra [27] and (iii) the W k algebra introduced in the context of fractional supersymmetric quantum mechanics of order k [28,30]. As a particular case, the algebra A {κ} with κ 1 = κ and r = 1 is nothing but the A κ algebra worked out in [18] and corresponding to…”
Section: The a {κ} Algebramentioning
confidence: 99%
“…The A {κ} r-parameter algebra covers the cases of (i) the extended harmonic oscillator algebra [21], (ii) the fractional oscillator algebra [27] and (iii) the W k algebra introduced in the context of fractional supersymmetric quantum mechanics of order k [28,30]. As a particular case, the algebra A {κ} with κ 1 = κ and r = 1 is nothing but the A κ algebra worked out in [18] and corresponding to…”
Section: The a {κ} Algebramentioning
confidence: 99%
“…2 by applying J ν=3 + three times on the ground state, Ψ k −3 ,0 (r, k −3 ), of V (−3) and obtain the third excited state of V (0). A more recent and detailed review of the SUSY formalism can be found in [19].…”
Section: Effective Morse Potentials Generated Bymentioning
confidence: 99%